The Psychological Impact of COVID-19 on Healthcare Providers in Obstetrics: A Cross-Sectional Survey Study - Del Piccolo, Lidia; Donisi, Valeria; Raffaelli, Ricciarda; Garzon, Simone; Perlini, Cinzia; Rimondini, Michela; Uccella, Stefano; Cromi, Antonella; Ghezzi, Fabio; Ginami, Maddalena; Sartori, Enrico; Ciccarone, Francesca; et al. (Frontiers in Psychology, 2021)
Objective: To assess the psychological distress of healthcare providers (HCPs) working in the field of obstetrics during the coronavirus disease 2019 (COVID-19) pandemic and to identify factors associated with psychological distress at the individual, interpersonal, and organizational level. Design: Cross-sectional survey study. Setting: Four University hospitals in Italy. Participants: HCPs working in obstetrics, including gynecologists, residents in gynecology and obstetrics, and midwives. Methods: The 104-item survey Impatto PSIcologico COVID-19 in Ostetricia (IPSICO) was created by a multidisciplinary expert panel and administered to HCPs in obstetrics in May 2020 via a web-based platform. Main Outcome Measures: Psychological distress assessed by the General Health Questionnaire-12 (GHQ-12) included in the IPSICO survey. Results: The response rate to the IPSICO survey was 88.2% (503/570), and that for GHQ-12 was 84.4% (481/570). Just over half (51.1%; 246/481) of the GHQ-12 respondents reported a clinically significant level of psychological distress (GHQ-12 ≥3). Psychological distress was associated with either individual (i.e., female gender, stressful experience related to COVID-19, exhaustion, and the use of dysfunctional coping strategies), interpersonal (i.e., lower family support, limitations in interactions with colleagues), and organizational (i.e., reduced perception of protection by personal protective equipment, perceived delays on updates and gaps in information on the pandemic) factors in dealing with the pandemic. Conclusions: Results confirm the need for monitoring and assessing the psychological distress for HCPs in obstetrics. Interventions at the individual, interpersonal, and organizational level may relieve the psychological distress during the COVID-19 pandemic and foster resilience skills in facing emotional distress.